Deterioration effects of coupled blisk blades. (10th October 2018) - Kellersmann, Andreas; Reitz, Gerald; Friedrichs, Jens
Abstract : Performance degradation due to wear of high pressure compressors (HPC) is a major concern in aero-engine operation and maintenance. Among other effects especially erosion of airfoils leads to changed aerodynamic behavior and therefore to deterioration. These affects engine performance parameter like thrust specific fuel consumption (TSFC) and exhaust gas temperature (EGT). Reaching EGT-limit, the engine typically has to be overhauled during a shop visit to restore safety standards and performance. During state of the art shop visits, engines are repaired based on EGT-specifications. To further enhance the maintenance, tailored repairs for each jet engine based on engine history and operation conditions are necessary to take TSFC into account. To ensure such an effective maintenance, the aerodynamic behavior of deteriorated and repaired airfoils is the key factors. Therefore, geometric properties with high influence on aerodynamic performance have to be known. For blisks (BLade-Integrated-diSK) the approach of tailored maintenance will be even more complicated because the airfoil arrangement cannot be changed or individual airfoils cannot be replaced. Thus, the effects of coupled misshaped airfoils have a high significance. This study will present a Design of Experiments (DoE) for circumferential coupled HPC-airfoils to identify the geometric properties which lead to a reduction of performance. To focus on geometric variations, quasi3D (Q3D) simulations are taken out. Based on a sensitivity analysis, the thickness related parameters, the stagger angle as well as the max. profile camber thickness are identified as the most important parameters which are influencing adjacent airfoils and reduce the aerodynamic performance.